FREE RADICAL SCAVENGING, ANTIOXIDANT POTENTIAL, AND NITRIC OXIDE INHIBITION IN HUMAN THP1 DERIVED MACROPHAGES BY KOKILAKSHAM KASHAYAM - TEENA MERLIN; PRAKASH KUMAR B (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study was to evaluate the antioxidant potential of Kokilaksham kashayam and its effect on the production of nitric oxide (NO) by lipopolysaccharide (LPS) stimulated THP1 derived macrophages. Methods: Kokilaksham kashayam was subjected to fractionation and assessed for antioxidant activity. The effect of fractions on cell viability was determined using 3-(4,5 – dimethylthiazol -2-yl)-2,5-diphenyltetrazolium bromide assay and the fractions were evaluated for their effect on the production of NO by LPS stimulated THP1 derived macrophages. Results: It was found that the fractions of the herbal decoction were able to scavenge a variety of free radicals 2,2-diphenyl-1-picrylhydrazyl, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid, NO, and hydroxyl radical. Ferric reducing antioxidant power assay showed the antioxidant capacity and cell culture studies in THP derived macrophages showed that the fractions inhibited the production of NO in LPS-stimulated THP1 derived macrophages. Conclusion: The overall study showed that the proinflammatory role of free radicals in general and specifically NO in chronic inflammatory condition could be managed by the use of Kokilaksham kashayam. The inhibitory effect of Kokilaksham kashayam on NO production and free-radical scavenging activity, in general, proves that the vital phytoconstituents in the herbal decoction are responsible for the antioxidant activity thereby preventing or slowing the process of chronic inflammatory conditions.